THE EFFECT OF THE SISKEUDES AND HUMAN RESOURCE COMPETENCY ON THE TRANSPARENCY OF THE VILLAGE GOVERNMENT BUDGET IN THE BATANG ASAM DISTRICT, TANJABAR REGENCY, JAMBI PROVINCE - Febriani, Ananda Fitri; Sam, Iskandar; Erwati, Misni (Jurnal Cakrawala Akuntansi, 2026)
Transparency in the management of village government budgets is an important aspect of good governance and public accountability in the management of village funds. The use of the Village Financial System (SISKEUDES) and the Competence of Village Human Resource are expected to support transparent financial management at the village level. This study aims to analyse the influence of SISKEUDES and Human Resource Competence on the transparency of village government budgets in Batang Asam Regency, Tanjung Jabung Barat Regency, Jambi Province. This study uses a quantitative approach with primary data collected through questionnaires distributed to village government officials. The research population included all villages in Batang Asam Regency, with a total sample of 88 respondents from 11 villages. The data were analyzed using multiple linear regression analysis, supported by data quality test and classical assumption test. The result showed that SISKEUDES and Human Resource Competencies together had a significant effect on budget transparency. Partially, SISKEUDES has a positive and significant effect, while Human Resource Competence does not have a significant effect. This study contributes to improving the understanding of technology supported village financial management in rural Indonesia and provides practical recommendations for policymakers to strengthen transparency in village financial management.